Pengaruh Kualitas Pelayanan, Harga Dan Citra Merek Terhadap Keputusan Pembelian Pada PT. Garuda Indonesia Semarang - Joko Azuardi; Mochamad Taufiq (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
In this era of globalization, there is development of the business world in the field of air transportation services. Many air transportation service companies have to compete for consumers through various strategies to win over consumers. The aim of this research is to analyze the influence of service quality, price and brand image on purchasing decisions. The population in this research is all consumers at PT. Garuda Indonesia Semarang in 2022, numbering 136,135 people, the sample was taken from 100 respondents using the Slovin formula. The data analysis tool used is multiple regression. The results of the analysis show that service quality has a positive effect on purchasing decisions, the higher the service quality, the higher the consumer's tendency to make purchasing decisions. Price has a positive effect on purchasing decisions, the more competitive the price, the higher the consumer's tendency to make purchasing decisions. Brand image has a positive effect on purchasing decisions, the better the brand image, the higher the consumer's tendency to make purchasing decisions. Research implications include the need to refresh employees, especially front liner staff, provide Cash Back or discounts using credit cards and implement Corporate Social Responsibility.